The essence and forms of international commerce - Novik, I. O.; Pererva, P. G. (Видавничий дім "Києво-Могилянська академія", 2023)
It has been proven that international trade allows countries to take advantage of competitive advantages in some areas while reducing disadvantages in others. . International trade differs technically from international trade only in that trade usually involves the buying and selling of goods and services, not the exchange of them. With the increasing globalization of business, international trade is becoming more popular and allows companies from less populated regions to compete with companies located in more populated regions.
Сутність і форми міжнародної торгівлі
Keywords: international trade; commerce; marketing; price; demand; supply; profit